Assessing disparities in health and living conditions: a comparative study of Hungarian-speaking Roma and non-Roma women across Hungary, Romania, and Slovakia - Mózes, Noémi; Takács, Johanna; Ungvari, Zoltan; Feith, Helga Judit (Frontiers in Public Health, 2024)
Background The Roma minority, Europe’s largest ethnic minority, experiences significant disparities in living conditions and health outcomes compared to the non-Roma populations across the continent. Despite extensive documentation of the socio-economic challenges faced by the Roma, there is a notable lack of comparative research. Methods This study aims to fill this gap by examining the differences in socio-economic characteristics, living conditions, and self-reported health status between Roma (R) and non-Roma (nR) women in in Hungary (HU), Romania (RO), and Slovakia (SK), providing a cross-country comparative analysis. Utilizing simple and multiple binary logistic models, our research analysed data collected from September 2020 to March 2022, involving 322 Roma and 294 non-Roma women in Hungary, 258 Roma and 183 non-Roma women in Romania, and 146 Roma and 163 non-Roma women in Slovakia. Results Findings indicate significant associations between increased age (R:OR = 1.04[1.02,1.06], p < 0.001), (nR:OR = 1.04[1.02,1.05], p < 0.001) lower financial situation (R:OR = 2.05[1.01,4.18], p = 0.048) (nR:OR = 1.67[1.01,2.77], p = 0.047), and basic education level (R:OR = 3.60[1.29,10.08], p = 0.015) (nR:OR = 3.64[1.77,7.51], p < 0.001) with the likelihood of poor health status across both groups in Hungary. In Romania, increased age (OR = 1.04[1.02,1.06], p < 0.001) and basic education level (OR = 5.24[2.29,11.99], p < 0.001) were particularly predictive of poor health among non-Roma, while in Slovakia, age (OR = 1.05[1.02,1.07], p < 0.001) was a significant factor for Roma, and intermediate education level (OR = 2.68[1.16,6.20], p = 0.021) was for non-Roma. The study also found that a higher number of children (HU:OR = 1.35[1.12,1.63], p = 0.002), (RO:OR = 1.57[1.25,1.96], p < 0.001) and problems with housing comfort (RO:OR = 4.83[2.19,10.62], p = 0.015) and wall conditions (RO:OR = 2.81[1.22,6.46], p < 0.001) significantly impacted the health status of non-Roma women in Hungary and Romania. Conversely, an increase in household size was associated with a better health status among Roma women in Hungary (OR = 0.88[0.79,0.99]) and Slovakia (OR = 0.78[0.61,0.99]). Conclusion By offering a novel comparative analysis, this study highlights the critical need for focused attention on the health disparities faced by Roma women, particularly those in a multiply disadvantaged situation due to their ethnic and socio-economic status.